Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have no idea what to do here, I believe what I am doing is mathematically correct but the book does not give the answer I am getting.

$$ \lim_{x\to 0} \; (1-2x)^{1/x}$$

For this I know that if I can make it the natural log (not sure why not just the log, but Stewart feels that isn't important to not so I will just blindly use the ln).

$$\frac{\ln(1-2x)}x$$

This is then very easy to calculate from here but I do not get the answer that I am suppose to. I get $2$ but I am suppose to get an answer of $e ^{-2}$

share|improve this question
    
1. What is the derivative of $\ln(1-2x)$? 2. Your limit calculation is for $\ln{f(x)}$, not your original function $f(x)$, what you need to do to $\ln{f(x)}$ to "get" $f(x)$? –  Salech Alhasov Apr 1 '12 at 2:28
    
I'll bet you did the derivative of $\ln(1-2x)$ incorrectly; did you remember to use the Chain Rule correctly? –  Arturo Magidin Apr 1 '12 at 2:28
    
Taking the derivative of a natural log is a lot cleaner. When you take the natural log of the limit, you are changing the value. Since $\ln x$ and $e^x$ are inverse functions, $e^{\ln x}=x$ Substitute your limit for $x$, then you can reverse the order of the limit and the natural log as Arturo did in his answer. Then you can use the necessary property of logarithms ($\ln a^b=b\ln a$)to get it into a form where you can apply l'Hopital's rule. –  Mike Apr 1 '12 at 6:34
    
I have a similar question, but with 2/x instead of 1/x. What do I do differently? –  cuabanana Apr 18 '13 at 22:44

2 Answers 2

up vote 4 down vote accepted

For $x$ close to $0$, $1-2x$ is positive. So $$(1-2x)^{1/x} = e^{\ln(1-2x)/x}.$$ Since the exponential function is continuous, $$\lim_{x\to 0} e^{\ln(1-2x)/x} = e^{\scriptstyle\left(\lim\limits_{x\to 0}\ln(1-2x)/x\right)}$$ provided the latter limit exists. So this lets you change the original problem into the problem of determining whether $$\lim_{x\to 0}\frac{\ln(1-2x)}{x}$$ exists, and if so what the limit is.

(Alternatively, since $\ln$ is continuous, $$\lim_{x\to 0}\ln\left((1-2x)^{1/x}\right) = \ln\left(\lim_{x\to 0}(1-2x)^{1/x}\right)$$ so you can do the limit of the natural log instead).

Now, the limit $$\lim_{x\to 0}\frac{\ln(1-2x)}{x}$$ is an indeterminate of type $\frac{0}{0}$, so you can try using L'Hopital's rule. We get $$\begin{align*} \lim_{x\to 0}\frac{\ln(1-2x)}{x} &= \lim_{x\to 0}\frac{(\ln(1-2x))'}{x'} &\text{(L'Hopital's Rule)}\\ &= \lim_{x\to 0}\frac{\quad\frac{1}{1-2x}(1-2x)'\quad}{1}\\ &= \lim_{x\to 0}\frac{(1-2x)'}{1-2x} \\ &= \lim_{x\to 0}\frac{-2}{1-2x}\\ &= -2. \end{align*}$$ Hence $$\begin{align*} \lim_{x\to 0}(1-2x)^{1/x} &= \lim_{x\to 0} e^{\ln(1-2x)/x}\\ &= e^{\lim\limits_{x\to 0}\ln(1-2x)/x}\\ &= e^{-2}. \end{align*}$$

share|improve this answer
    
I don't understand where e is coming from. –  user138246 Apr 1 '12 at 3:30
    
@Jordan: By definition, for $a\gt 0$, we have $$a^b = e^{b\ln a}.$$ Alternatively, simply note that $e^{\ln x} = x$ for all $x\gt 0$, so $$a^b = e^{\ln(a^b)} = e^{b\ln(a)}.$$ –  Arturo Magidin Apr 1 '12 at 3:31

Let’s write out what’s really going on. You have $$L=\lim_{x\to 0}\;(1-2x)^{1/x}\;.$$ You take logs and use the continuity of the log function to get

$$\ln L=\ln\lim_{x\to 0}\;(1-2x)^{1/x}=\lim_{x\to 0}\;\frac1x\ln(1-2x)=\lim_{x\to 0}\;\frac{\ln(1-2x)}x\;.$$

Now you use l’Hospital’s rule to say that

$$\ln L=\lim_{x\to 0}\;\frac{\frac{-2}{1-2x}}1=\lim_{x\to 0}\frac{-2}{1-2x}=-2\;.$$

But this isn’t the original limit $L$: this is $\ln L$. To get $L$, you must exponentiate:

$$L=e^{\ln L}=e^{-2}\;.$$

share|improve this answer
    
I don't know what you mean by L and how you are making the e ln L be -2. –  user138246 Apr 1 '12 at 3:29
    
@Jordan: $L$ is defined in the first displayed line: it’s simply a short name for the limit $\lim_{x\to 0}\;(1-2x)^{1/x}$. It’s easier to write $L$ than to keep writing $\lim_{x\to 0}\;(1-2x)^{1/x}$. I did not say that $e^{\ln L}$ was $-2$; $\ln L$ is $-2$, and $L$ is $e^{\ln L}$, so $L=e^{-2}$. –  Brian M. Scott Apr 1 '12 at 3:33

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.